Onion‐like Multifunctional Microtrap Vehicles for Attraction–Trapping–Destruction of Biological Threats. (20th January 2020) - Soto, Fernando; Kupor, Daniel; Lopez‐Ramirez, Miguel Angel; Wei, Fanan; Karshalev, Emil; Tang, Songsong; Tehrani, Farshad; Wang, Joseph
Abstract: A multifunctional motile microtrap is developed that is capable of autonomously attracting, trapping, and destroying pathogens by controlled chemoattractant and therapeutic agent release. The onion‐inspired multi‐layer structure contains a magnesium engine core and inner chemoattractant and therapeutic layers. Upon chemical propulsion, the magnesium core is depleted, resulting in a hollow structure that exposes the inner layers and serves as structural trap. The sequential dissolution and autonomous release of the chemoattractant and killing agents result in long‐range chemotactic attraction, trapping, and destruction of motile pathogens. The dissolved chemoattractant (l ‐serine) significantly increases the accumulation and capture of motile pathogens (E. coli) within the microtrap structure, while the internal release of silver ions (Ag + ) leads to lysis of the pathogen accumulated within the microtrap cavity. Abstract : Eine multifunktionale Mikrofalle kann durch kontrollierte Chemoattraktoren und Freigabe therapeutischer Wirkstoffe autonom Pathogene anlocken, einfangen und zerstören. Die mehrlagige Struktur enthält einen Mg‐Kern, Chemoattraktoren im Inneren sowie Therapeutika‐Schichten. Durch chemischen Antrieb wird der Mg‐Kern verbraucht, was eine Hohlstruktur erzeugt, die als Falle fungiert und in der die inneren Schichten freiliegen.